Assessment of Helicobacter pylori vacA and cagA Genotypes and Host Serological Response - Figueiredo, Céu (American Society for Microbiology, 2001)
Helicobacter pylori strains can be distinguished by genotyping of virulence-associated genes, such as vacA and cagA. Because serological discrimination between strain types would reduce the need for endoscopy, 61 patients carrying H. pylori were studied by vacA and cagA genotyping of H. pylori in gastric biopsy specimens and by detection of specific serum antibodies. Serological responses to H. pylori were determined by Helicoblot (versions 2.0 and 2.1). Antibodies to CagA also were determined by a rapid anti-CagA assay (Pyloriset screen CagA) as well as by two noncommercially developed enzyme immunoassays, each using a recombinant CagA protein. Assessment of performance of the Helicoblot assays indicated substantial interobserver variation, with kappa values between 0.20 and 0.93. There was no relationship between the serological profiles on the Helicoblot and the genotypes from the same patients, except for strong associations between the presence of anti-CagA and the cagA-positive and vacA s1 H. pylori genotypes. Detection of anti-CagA by the five different assays varied considerably, with kappa values ranging from 0.21 to 0.78. Using the cagA genotype as the “gold standard,” the sensitivity and specificity of the anti-CagA assays varied from 71.4 to 85.7% and from 54.2 to 100%, respectively. Thus, serological profiles of antibodies to H. pylori are heterogeneous and, with the exception of anti-CagA antibodies, show no relation to the H. pylori vacA and cagA genotypes. Detection of anti-CagA antibodies is strongly dependent on the test used.